2012
DOI: 10.1136/jnnp-2012-303821
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-wise mapping of cervical cord damage in multiple sclerosis patients with different clinical phenotypes

Abstract: Voxel-based assessment of cervical cord damage is feasible and may contribute to a better characterisation of the clinical heterogeneity of MS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…Morphometry studies using statistical mapping methods have so far only been performed on the cord itself to study SC atrophy in MS patients (Rocca et al, 2013;Valsasina et al, 2013) or aging (Valsasina et al, 2012). While demonstrating the feasibility of SC Voxel-Based Morphometry, potential GM alteration was not assessed in these studies, mainly because of a lack of contrast on the sequence used (T 1 -weighted acquisitions), but more generally, because of a lack of post-processing tools such as white and gray matter templates and common space for registration.…”
Section: Spinal Cord Tbm For Age-related Changes Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphometry studies using statistical mapping methods have so far only been performed on the cord itself to study SC atrophy in MS patients (Rocca et al, 2013;Valsasina et al, 2013) or aging (Valsasina et al, 2012). While demonstrating the feasibility of SC Voxel-Based Morphometry, potential GM alteration was not assessed in these studies, mainly because of a lack of contrast on the sequence used (T 1 -weighted acquisitions), but more generally, because of a lack of post-processing tools such as white and gray matter templates and common space for registration.…”
Section: Spinal Cord Tbm For Age-related Changes Characterizationmentioning
confidence: 99%
“…Nonetheless, although both VBM and TBM are widely used in neuroimaging to study brain structural alterations, their application in spinal cord studies have been very sparse and limited to the cord itself, without tissue-specific information on the WM and GM (Rocca et al, 2013;Valsasina et al, 2012Valsasina et al, , 2013 mainly because of the lack of robust automated GM segmentation method and proper non-linear normalization procedures. Having such tools at disposal would allow subtler morphometric studies of regional structural alterations in the SC and thereby give an increased understanding of some neurodegenerative processes occurring with age or central nervous system (CNS) pathologies such as amyotrophic lateral sclerosis (ALS), which specifically affects cortical and spinal motor neurons, as well as corticospinal tracts.…”
Section: Introductionmentioning
confidence: 99%
“…The use of this method in a multicenter study to investigate the correlation between cord atrophy and clinical disability in a large sample of MS patients has demonstrated that CSA differs significantly among the main MS clinical phenotypes and it is correlated with EDSS, with a differential effect among disease clinical phenotypes: no association in either CIS patients or in benign MS; association in RRMS, SPMS and primary progressive (PP) MS (Rocca et al, 2011). Combining the AS method with voxel based analysis of structural scans of the spinal cord has the potential to provide an insight into localized changes in patients with MS (Rocca et al, 2013; Valsasina et al, 2013). These results suggest that cervical cord atrophy provides a relevant and useful marker for the characterization of clinical heterogeneity of MS patients.…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Previous spinal cord voxel-based analyses have relied on sagittal-based registration. 9 Axial imaging can provide higher cross-sectional resolution than sagittal imaging for anisotropic voxel dimensions. We defined upper and lower limits of C1 and C5 individually to maintain some degree of longitudinal anatomical correspondence.…”
mentioning
confidence: 99%